1998
DOI: 10.1016/s0005-2728(98)00088-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of threonine structural changes upon formation of the M-intermediate of bacteriorhodopsin: evidence for assignment to Thr-89

Abstract: The behavior of threonine residues in the bacteriorhodopsin (bR) photocycle has been investigated by Fourier transform infrared difference spectroscopy. L-Threonine labeled at the hydroxyl group with 18O (L-[3-(18)O]threonine) was incorporated into bR and the bR-->M FTIR difference spectra measured. Bands are assigned to threonine vibrational modes on the basis of 18O induced isotope frequency shifts and normal mode calculations. In the 3500 cm-1 region, a negative band is assigned to the OH stretch of threoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
8
3
Order By: Relevance
“…In the M intermediate of BR, some intensity changes at 1130–1110 cm –1 were observed to shift with [3- 18 O]­Thr-labeling, probably originating from the COH bending of Thr . However, even with isotopic labeling, it was not possible to clearly resolve the affected bands.…”
Section: Integration and Interpretationmentioning
confidence: 95%
See 1 more Smart Citation
“…In the M intermediate of BR, some intensity changes at 1130–1110 cm –1 were observed to shift with [3- 18 O]­Thr-labeling, probably originating from the COH bending of Thr . However, even with isotopic labeling, it was not possible to clearly resolve the affected bands.…”
Section: Integration and Interpretationmentioning
confidence: 95%
“…In practice, all the six carbon atoms have been labeled using [ 13 C 6 ]-His, , the three nitrogen atoms labeled using [ 15 N 3 ]-His, or all carbon and nitrogen atoms have been labeled using [ 13 C 6 , 15 N 3 ]-His . In the case of Thr, [3- 18 O]­Thr has been used to assign side chain νO–D and δCOH vibrations. ,, Finally, the N–H stretch from the indole group of Trp was assigned using [indole- 15 N]­Trp …”
Section: Tools For Band Assignmentmentioning
confidence: 99%
“…For example, the L intermediate in BR gives rise to an NH stretch mode in the tryptophan indole group at 3,477 cm −1 [50]. A positive band near 3,511 cm −1 and smaller features at 3,496 cm −1 (−) were assigned in the BR→M difference spectrum to a threonine residue (OH stretch) on the basis of [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] O]Thr labeling, while a much smaller band appearing at 3,486 cm −1 was tentatively assigned to a tryptophan [51] (NH stretch). The appearance of bands at the same position in AR3 indicated that similar residues undergo similar structural changes in AR3.…”
Section: Structural Changes Of Weakly Hydrogen Bonded Internal Water mentioning
confidence: 99%
“…Bands assigned to particular amino acids are equally unaffected. Examples include peaks due to Asp-85 at 1761 cm ÿ1 (þ), Asp-96 at 1742 cm ÿ1 (ÿ) (Braiman et al, 1988a;Maeda et al, 1992b), Tyr-185 at 1276 cm ÿ1 (ÿ) and 1271 cm ÿ1 (þ) (Braiman et al, 1988b;Roepe et al, 1987;Rothschild et al, 1986), Thr-89 near 1125 cm ÿ1 (Liu et al, 1998); and Trp in the 740 cm ÿ1 region (Roepe et al, 1988) and at 3486 cm ÿ1 (Maeda et al, 1992a) (data not shown). The vibrational bands assigned to at least one water molecule, most likely located in the active site of BR (Brown et al, 1994), are also not altered by the SeMet substitution (data not shown).…”
Section: Ftir Difference Spectroscopymentioning
confidence: 97%